Comparative Review of the Features of Automated Software Testing Tools - Heidilyn Veloso Gamido; Marlon Viray Gamido (Institute of Advanced Engineering and Science, 2019)
Software testing is considered to be one of the most important processes in software development for it verifies if the system meets the user requirements and specification. Manual testing and automated testing are two ways of conducting software testing. Automated testing gives software testers the ease to automate the process of software testing thus considered more effective when time, cost and usability are concerned. There are a wide variety of automated testing tools available, either open source or commercial. This paper provides a comparative review of features of open source and commercial testing tools that may help users to select the appropriate software testing tool based on their requirements.